1997
DOI: 10.3354/meps148037
|View full text |Cite
|
Sign up to set email alerts
|

Spawning stock dynamics of two penaeid prawns, Metapenaeus bennettae and Penaeus esculentus, in Moreton Bay, Queensland, Australia

Abstract: ABSTRACT. Spawning stock dynamics of 2 commercially important penaeid prawns, Metapenaeus bennettae and Penaeus esculentus, from 9 stations in Moreton Bay (27" 15'S, 153'15'E), southeast Queensland, Australia, were examined. An egg production index (EPI), based on the relative abundance, proportion that were mature or ripe, and s u e of adult females, was used as a measure of e g g production in the 2 populations. Egg production by M. bennettae was 20 to 30 higher than that by P esculentus, extended over 7 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…Besides the influence on the period of the reproductive cicle, temperature also plays an important role on size at first maturity, in such a way that populations distributed in higher latitudes have later gonadal development and therefore reach larger LM (Courtney & Massel 1997). Comparison of mean length at first maturity of population inhabiting Southern Brazil (16.76mm) to investigations performed in northern and southern limits of distribution confirms this pattern.…”
Section: Seasonal Reproductive Dynamics and Size At First Maturitysupporting
confidence: 58%
“…Besides the influence on the period of the reproductive cicle, temperature also plays an important role on size at first maturity, in such a way that populations distributed in higher latitudes have later gonadal development and therefore reach larger LM (Courtney & Massel 1997). Comparison of mean length at first maturity of population inhabiting Southern Brazil (16.76mm) to investigations performed in northern and southern limits of distribution confirms this pattern.…”
Section: Seasonal Reproductive Dynamics and Size At First Maturitysupporting
confidence: 58%
“…It is known that in closed thelycum species, the plot of the percentage insemination in each size class results in a more or less sigmoidal relationship, e.g., P. esculentus, P. semisulcatus (Crocos 1987a, b), M. longistylus, M. latisulcatus (Courtney and Dredge 1988), F. merguiensis (Crocos and Kerr 1983). However, contrasting results are reported even for the same species, as sigmoidal curve is not presented in P. esculentus by Courtney and Masel (1997). Moreover, although insemination increases with size, a typical sigmoidal curve is not shown in .…”
Section: Spermatophore Inseminationmentioning
confidence: 68%
“…Interannual and monthly variations in reproductive activity of many other penaeid species have been reported (e.g. Courtney and Masel 1997;Crocos and van der Velde 1995;Minagawa et al 2000;Montgomery et al 2007;Hossain and Ohtomi 2008).…”
Section: Spawning Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…This, however, should be considered a biased index of reproduction, which should be modified by an index that includes both abundance data and data on fecundity-at-size (García, 1985). Courtney & Masel (1997) proposed an egg production index, EPI, composed of fecundity-at-size data, and data on the proportions of mature females. They found that this new index is a more quantitative measure of egg production in a population at a particular sampling station or sampling time.…”
Section: Introductionmentioning
confidence: 99%